Problem Solving in Genetics: Conceptual and Procedural Difficulties - (:unkn) unknown (EDAM, 2011)
The purpose of this study was to explore prospective biology teachers' understandings of fundamental genetics concepts and the association between misconceptions and genetics problem solving abilities. Specifically, the study describes conceptual and procedural difficulties which influence prospective biology teachers' genetics problem solving abilities. Case study methods were utilized in this study. Total of 70 prospective biology teachers participated in this study. The data sources included genetics concept tests (GBT) and semi-structured interviews. Genetics concept tests were administered to all of the participants. Six participants were selected by purposeful sampling for semi-structured interviews. The results of the study showed that prospective biology teachers had incomplete understandings and several alternative conceptions of Mendelian genetics. Although they were able to describe some concepts, they frequently failed to apply them in problem solving situations. In many cases mechanical application of common problem solving strategies were observed without comprehensive conceptual understanding. The participants that demonstrated behaviors which require metacognitive strategies and higher order thinking skills such as constructing hypothesis, data, and end-means analysis were more successful in genetics problem solving. Some of the participants who were successful in cause-effect type problems had difficulties in end-means type of problems.
Keywords: Genetics Learning; Problem Solving in Genetics; Biology Teacher Education; LEARNING-DIFFICULTIES; SCHOOL-STUDENTS; CELL-DIVISION; BIOLOGY; MISCONCEPTIONS; TEACHERS